ANALISIS PENGARUH EARNING PER SHARES (EPS), PRICE TO BOOK VALUE (PBV), RETURN ON EQUITY (ROE), RETURN ON INVESTMENT (ROI) DAN PRICE EARNING RATIO (PER) TERHADAP HARGA SAHAM PADA PERUSAHAAN METAL AND ALLIED PRODUCT DI BURSA EFEK INDONESIA - Mei Ayu Warti; Salamatun Asakdiyah (Universitas Ahmad Dahlan, 2014)
This study aims to determine the influence of Earning Per Share (EPS), Price to Book Value (PBV), Return On Equity (ROE), Return On Investment (ROI), and Price Earning Ratio (PER) towards the stock price at Metal andd Allied Product Companies in Indonesia Stock Exchange. The population in this study amouted to 14 companies, and by using sampling techniques in the form of purposive sampling acquired 11 companies which can be sampled. Source of data used in this research is secondary data derived from Indonesian Capital Market Directory (ICMD) in 2005 until 2009. Data analysis in this study using multiple linear regression analysis and t test. The result of analysis is the EPS has significant influences on stock price with value of 0.000 < 0.05, PBV has a significant influence on stock price with a value 0.000 < 0.05,Â ROE does not have a significant influence on stock price with a value of 0.141 > 0.05, ROI does not have a significant influence on stock price with a value of 0.913 > 0.05, and PER does not have a significant influence on stock price with a value of 0.154 > 0.05. value of R Square shows the results 0.720, which means 72% of the stock price can be explained by the variable EPS, PBV, ROE, ROI, and PER, while the remainder, 28% of stock price is explained by other independent variables are not observed/assumed to be constant.